Colonial Policy, Ecological Transformations, and Agricultural “Improvement”: Comparing Agricultural Yields and Expansion in the Spanish and U.S. Philippines, 1870–1925 CE - Findley, David Max (Archīum Ateneo, 2024)
Burgeoning global trade and colonial policies promoted transformations in land use and agriculture throughout tropical regions in the 19th and 20th centuries, but the local and regional ecological consequences of landscape changes are still being identified and analysed. The Philippine Archipelago, which experienced successive colonial regimes across more than 7100 islands, exemplifies the multiplicity of ecological outcomes produced by these transformations. To better characterise diverse landscape change, we use colonial censuses and datasets to assess land use, production and agricultural yields in the Philippines during the late Spanish and early U.S. colonial periods (ca. 1870–1925). Our novel digital, quantitative analysis indicates that, at the national and provincial scales, agricultural production and land use increased for all major crops in both periods, while agricultural yields were mostly constant. Our results suggest that colonial investments to “improve” Philippine agriculture, specifically their efforts to increase production per hectare, were not effective. Our provincial-scale analysis also confirms the importance of distinct labour patterns, geographies and socio-political arrangements in defining this period’s ecological consequences, and we provide quantified and historically contextualised data in a format amenable to ecologists to promote future, localised historic ecological research.